Volume of the hyperbolic cantor sets. Issue 2 (2nd April 2020) - Akhadkulov, Habibulla; Jiang, Yunping
ABSTRACT: In this paper, we study hyperbolic Cantor sets on the line. We prove that the Lebesgue measure of a hyperbolic Cantor set generated by a degree two expanding map satisfying a certain Zygmund condition is zero. Moreover, we show that for any ρ ∈ ( 0, 1 ) there exists a C 1 -smooth degree two expanding map f such that the Lebesgue measure of the hyperbolic Cantor set generated by f is ρ .